PENGARUH PENAMBAHAN POLIMER EMULSI VINYL ACECATE CO ACRYLIC PADA TANAH LEMPUNG TERHADAP UJI PERMEABILITAS MELALUI CONSTANT HEAD PERMEABILITY TEST - Halauddin, Halauddin; Suhendra, Suhendra (BERKALA FISIKA, 2011)
Permeability is rate of movement an fluid in soil through a media  have relation pore micro and macro way, happen of vertical and horizontal. Permeability of soil depend on pore mean size measure influenced by particle size measure distribution, viscosity, particle form and soil structure. Smaller soil particle size measure, smaller also pore size measure and progressively lower ability of the soil to overcome fluid. This research aim to know the level of permeability coefficient value of soil residing in gristle area slide by pass Bengkulu Kepahiang by using method permeameter of permeability head constant by comparing given by permeability value is emulsion polymer and do not give by type emulsion polymer of  poly vinyl acetate co acrylic (PVA). This research have done in laboratory have the character of pure experiment and conducted sometime. From result of research, obtained that: value permeability of biggest soil before given by emulsion polymer of PVA there are at location III equal to 8,62.10-3 cm/s, and value permeability of smallest soil before given by emulsion polymer there are at location I equal to 3,87.10-3 cm/s. While value permeability of biggest soil after given by emulsion polymer of PVA there are at location V equal to 0,96.10-3 cm/s, and value permeability of smallest soil after given by emulsion polymer there are at location IX equal to 0,10.10-3 cm/s.   Keywords: Permeability, constant head permeability, pore of size,  polymer of emulsion and                     poly vinyl acetate co acrylic (PVA).